Faktor-Faktor yang Mempengaruhi Preferensi Masyarakat Bermukim di Kecamatan Somba Opu, Kabupaten Gowa - Muh Alfiansyah A; Wiwik Wahidah Osman; Shirly Wunas (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Factor of Community preference to stay in Sub district Somba Opu caused the high demand for settlement land, it triggered the occurrence of land conversion. This research aim to: 1) identify the coversion of agriculrural land into developing area in past 10 years (2008-2018); 2) identify community preference factors for living in Somba Opu District; and 3) arranging the direction of development in Somba Opu District in preventing land conversion. The primary data is obtained by using Landsat 7 ETM maps and secondary data obtained from interviews of people living in the research location. Spatial analysis was used to determine changes in spatial function change using arcgis applications, multiple linear regression analysis was used to determine the most dominant factors in the occurrence of land conversion, and comparative analysis was used to compare problems and directives that should be done. The results showed that in the last 10 years (2008-2018) the conversion of agricultural land into development area in Somba Opu Disctrict initially in 2008 has broadly 15.29 Km2 reduced to 12,48 Km2 in 2018. In addition, In addition, the result is the most influential factor is the location of the land of Somba Opu District which is directly adjacent to the city of Makassar and is located on side of the road connecting Gowa Regency and Makassar City. So to control preference factor wich caused the high demand for settelemant land is the review of the RTRW and the completion of the Gowa Regency RDTR, the implementation of zoning, and the provision of incentives and disincentives must be done.